RELIGIOUS MODERATION IN THE FRAMEWORK OF LIFE - Muchtar, Choiriyah; Dwi Noviani; Mardeli; Mutiara; Manna Dey (The Islamic Education and Multiculturalism Foundation, 2022)
This study concludes conclusion of this study is that extremism in the name of religion can be eradicated through moderate and inclusive Islamic education. Religious moderation can be expressed through tawazun (balance), i'tidal (truth and stability), tasamuh (tolerance), musawah (equality), shura (consideration), ishlah (equality) reform), aulawiyah (priority), tathawwur wa ibtikar ( dynamic and creative). For this reason, an attitude of religious moderation is needed which includes acknowledging the existence of other parties, being tolerant, respecting differences of opinion, and not forcing one's will by force. The role of the government, community leaders, and religious educators is needed to socialize and develop community religious moderation to create harmony and peace.